Common Endpoints for Suzuki Mappings in Uniformly Convex Hyperbolic Spaces: Aekkarin Kudtha, Bancha Panyanak - Team, Support (Thai Journal of Mathematics, 2023)
The existence of endpoints for Suzuki mappings in uniformly convex hyperbolic spaces is proved. A common endpoint theorem for a commuting pair of single-valued and multivalued Suzuki mappings is also established.